Abdominal colour polymorphism in female asian golden web spider nephila antipodiana (araneae: nephilidae) - Hashim, Rosli; Eem, L.P.; Sen, Y.H.; Belabut, D. (2010)
Nephila antipodiana (Batik Golden Web Spider) occurred in large numbers in several localities in Kelantan and Terengganu, east coast of Peninsular Malaysia. Three abdominal (opisthosomal) colour morphs - yellow, greenish-yellow and reddish-brown - were present in adult female spiders. Only two colour morphs appear to be present in a particular locality. The yellow morph occurred in all the localities investigated. Of the two non-yellow morphs, the reddish-brown morph was found only in one locality while the greenish-yellow morph was more widespread. The present study does not show unequivocally the association of colouration with habitat usage. Whether yellow colour in N. antipodiana confers a selective advantage remains to be verified. In addition to opisthosomal colour polymorphism, the colour and number of spots (or sigillae) on the dorsal surface of the abdomen of female N. antipodiana are also variable. The juvenile spiders have different colour pattern from the adults.